2017
DOI: 10.1002/ejoc.201700801
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Iridium(III) Metallacycle Catalyst for the Effective Hydrosilylation of Carbonyl and Carboxylic Acid Derivatives

Abstract: A versatile iridium(III) metallacycle catalysed rapidly and selectively the reduction of a large array of challenging esters and carboxylic acids as well as various ketones and aldehydes. The reactions proceeded in high yields at room temperature by hydrosilylation followed by desilylation. Although the reactions of various aldehydes and ketones resulted exclusively in alcohols, the hydrosilylation of esters led to alcohols or ethers, depending on the type of substrate. Regarding the carboxylic acids, again th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 127 publications
1
16
0
Order By: Relevance
“…The corresponding results are available in Schemes S4 and S5 in the Supporting Information. These results show that the hydrosilylation of carbonyls operates with precatalyst loads of 0.05–2 mol %, producing the resulting triethylsilyl ethers in yields >90% in most cases, this without the use of any additive …”
Section: Resultsmentioning
confidence: 99%
“…The corresponding results are available in Schemes S4 and S5 in the Supporting Information. These results show that the hydrosilylation of carbonyls operates with precatalyst loads of 0.05–2 mol %, producing the resulting triethylsilyl ethers in yields >90% in most cases, this without the use of any additive …”
Section: Resultsmentioning
confidence: 99%
“…35 The observation that 2/NaBAr F 4 catalyzes the hydrosilylation of carbonyl derivatives 39,40 and dehydrosilylation of alcohols 30 in the dark but does not catalyze hydrosilylative ether cleavage in the absence of light can be interpreted in the context of the relative reactivities of the plausible reaction intermediates. These three transformations share similar mechanisms, with heterolytic Si−H cleavage giving silyloxycarbenium 38,39 and mono- 30 and dialkylsilyloxonium 34,35,47 ions, respectively. Our observation that the catalyst resting state after illumination is a mixture of the neutral monohydride complex 5 and the dimeric monohydride 6 is consistent with a catalytic cycle resting at the silyloxonium/5 reactant pair (with 5 in equilibrium with 6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Further optimization of the reaction conditions demonstrated that the parent chloride compound 2 gives a more effective catalytic system in the presence of NaBAr F 4 , which presumably effects chloride abstraction to give cationic intermediates. These conditions allow for high yields with as little as 5 mol % of 2 . Compound 2 is unreactive in the absence of NaBAr F 4 (Table , entries 3 and 4), which would be expected if the reaction proceeds via a cationic σ-silane intermediate similar to those previously reported for other ether cleavage catalysts. ,, NaBAr F 4 can be substituted by [Ph 3 C]­[BAr F 4 ] with a similar catalytic performance (entry 5), but this reagent offers no clear benefit over the stable, commercially available sodium salt.…”
Section: Resultsmentioning
confidence: 99%
“…The same group also reported an interesting Ir(III) metallacycle 94 as catalyst for hydrosilylation of various ketones and aldehydes in the presence of sodium tetrakis[(3,5trifluoromethyl)phenyl]borate (NaBArF 24 ) under mild conditions (Scheme 43-44). [89] This complex was also able to catalyse selectively the reduction of esters and carboxylic acids (Scheme 45), resulting in, depending on the substrate, either alcohols/ethers or alcohols/aldehydes, respectively. The authors proposed an ionic hydrosilylation pathway, which starts from metathesis of the pre-catalyst 94 with NaBArF 24 to form a cationic complex.…”
Section: Achiral Hydrosilylationmentioning
confidence: 99%